Design of a Tray Dryer Machine - Syahwiranda Nasution; Devi Tanggasari (Universitas Muhammadiyah Mataram, 2024)
The Tray Dryer is one of the most widely used batch-type drying tools due to its simple design. The configuration of the tray dryer consists of an arrangement of several racks with a convection drying system, where hot air is circulated onto the racks in a space to dry the products. The tray dryer is capable of reducing the drying area dimensions and improving the contact of hot air with the material, making the drying process adjustable. The purpose of this research is to understand how to determine the methods and design a tray dryer drying machine. The design of this tray dryer drying machine utilizes Solidworks software, comprising both structural and functional design. The temperature distribution of the tray dryer machine has the highest temperature on the top rack because the fan is less efficient in promoting temperature uniformity across each drying rack. Thus, testing on the drying machine varies, where on the first rack, the temperature reaches 50°C, while on the second rack, it decreases to 49°C, and on the third rack, it is 45°C. This led to testing with the material of cherry leaf with an initial moisture content of 64.2%, obtaining moisture content after 90 minutes of drying on the first rack at 47.33%, on the second rack at 48.3%, and on the third rack at 53.6%. So, in the testing process, different results are obtained for each rack.